Citrus Mealybug Planococcus citri (Risso) (Insecta: Hemiptera: Pseudococcidae) - Harsimran Kaur Gill; Gaurav Goyal; Jennifer Gillett-Kaufman (EDIS)
The citrus mealybug is a common pest of citrus primarily in greenhouses, and of several ornamental plants in Florida. It has been recognized as a difficult to control pest in Europe since 1813, where it is called the greenhouse mealybug, and in the United States since 1879. This 4-page fact sheet was written by Harsimran Kaur Gill, Gaurav Goyal, and Jennifer Gillett-Kaufman, and published by the UF Department of Entomology and Nematology, September 2012.